Kekristenan dan Tradisi Ru-ketu “Tinjauan Tipologi Helmut Richard Niebuhr Terhadap Pandangan Pro-Kontra Praktek Tradisi Ru-ketu Di kalangan Komunitas Kristen Sabu Barat Kabupaten Sabu Raijua” - Osian Orjumi Moru (Institut Agama Kristen Negeri Kupang, 2022)
This article aims to describe Helmut Richard Niebuhr's typology review of the pros and cons of the practice of the ru-ketu tradition among the Christian community of Sabu Barat, Sabu Raijua district. The research method used to describe this article is a qualitative method with interview and literature studies techniques. The data obtained from the research results are then analyzed using descriptive analysis techniques. The results showed that there were three groups of respondents perceptions of the Sabu Barat Christian community towards the practice of the ru-ketu tradition based on Helmut Richard Niebuhr's typological classification. The first group is a minority group that tends to be dualistic and ambiguity. This attitude is due to the strong influence of genealogical factors. The second group is the majority group that tends to have a transformative view of the ru-ketu tradition. The perception of this group tends to be influenced by two factors at once, namely cultural factors and religious identity factors. This group tends to practice the ru-ketu tradition with a number of adaptation changes in the stages of implementation due to the influence of Christian religious teachings. The third group is a small number of respondents who tend to be antipathetic and reject the involvement of the Christian community in the implementation of the ru-ketu tradition. This group tends to position the Christian religious entity as an entity that is contrary to the ru-ketu tradition because of the exclusive religious doctrine factor.